An Islamic jihad of nonviolence: Said Nursi's model - Sayilgan, Salih (Cascade Books, 2019)
Part 1. Said Nursi: Said Nursi's Life and Context -- The Story of the Risale-i Nur -- Part 2. An Islamic Jihad of Nonviolence: Jihad in Islamic Thought -- Foundation of Jihad of Nonviolence: Positive Action -- Elements of Inward Jihad -- Enemies Redefined: Reinterpretation of Outward Jihad -- Guidelines for the Community of Believers -- Nursi in Conversation with Gandhi, King, and Mandela -- Conclusion -- Appendix: A portion from Nursi's Last Teaching to the Students of the Risale-i Nur before His Death.